Understanding tuberculosis as a wicked problem: a qualitative study in coastal urban settlements of Semarang, Indonesia - Shaluhiyah, Zahroh; Handayani, Sri; Sriatmi, Ayun; Agushybana, Farid; Rimawati, Eti (Frontiers in Communication, 2025)
IntroductionIn Indonesia, tuberculosis (TB) remains a significant public health challenge. In coastal urban areas, where poverty, overcrowding, stigma, and inadequate health infrastructure intersect, TB emerges through a network of social, cultural, environmental, and institutional vulnerabilities. This study explored TB as a wicked problem in urban coastal settlements, where issues related to structures, culture, and communication all interact, making it harder to control the disease effectively.MethodsA qualitative exploratory study was conducted in Semarang’s coastal urban settlements, which were identified as high-risk areas for TB. In-depth interviews were done with 27 participants, including TB patients, household contacts, health cadres, health staff, local stakeholders, and community members. Data were analyzed thematically, focusing on how social, cultural, and institutional factors shaped TB vulnerability and control.ResultsSix interrelated identifiers TB as a wicked problem in coastal area emerged: (1) euphemistic and stigmatized communication, with widespread avoidance of the term “TB”; (2) symptom mis-recognition, where coughing and fatigue were normalized or overlooked; (3) structuring stigma, reinforcing social silence and delayed disclosure; (4) culturally embedded illness narratives, including moral, spiritual, and lifestyle explanations; (5) Perceptions of health based on functionality, where health was defined by the ability to perform daily activities, often minimizing the urgency of treatment; and (6) fragmented health system responses, including under-resourced outreach, unaligned service hours, and superficial health education. These factors interact within a fragile coastal environment characterized by tidal flooding, high humidity, and overcrowding, which collectively increase TB exposure. Unlike in mountainous areas, coastal communities face compounded ecological and institutional vulnerabilities.ConclusionEfforts to eliminate TB in Indonesia must go beyond biomedical solutions to address the complex interplay of cultural beliefs, environmental vulnerability, and systemic health system weaknesses. Adaptive, multisectoral, and culturally informed interventions are urgently needed to tackle TB as a wicked problem in coastal urban contexts.